Peningkatan SDM Melalui Pelatihan Kepenulisan dan Self-Publishing Bagi Generasi Muda Sengkang Kab. Wajo - Sumangelipu, Andi (JOURNAL OF TRAINING AND COMMUNITY SERVICE ADPERTISI (JTCSA), 2023)
Increasing human resources or HR is achieved by development methods related to knowledge, skills and abilities through education and training, in this case training. Writing and self-publishing training for the young generation aims to improve (1) literacy skills, (2) ability to process information, (3) ability to disseminate and publish information through self-publishing. This activity was carried out on September 10-11, 2023 and was attended by 20 young people from HMI Wajo Maju Branch, Wajo Regency.